2018
DOI: 10.1149/2.1011803jes
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study of the Initial Lithiation of Amorphous Silicon Thin Film Anodes

Abstract: The mechanisms and kinetics of lithiation and delithiation of amorphous silicon were investigated using potentiostatic techniques and thin films of different thickness, with a focus on the initial lithiation process that occurs in the first cycle. In potentiostatic tests, distinct kinks were observed in the current vs. time curves, and the time at which the kink occurred increased for thicker films. This behavior can be explained using a model in which a sharp interface between an amorphous Li x Si phase and L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…The equilibrium crystalline phases are bypassed due to higher barriers to their nucleation compared with those of the metastable amorphous phases [16]. Similar phenomena are also observed in other alloying anodes, as well as LiMPO 4 [17,18] and Li 2 MSiO 4 [19] cathodes, for varying metals M. The mechanism of the first-cycle lithiation of Si has been intensively studied using in situ transmission electron microscopy (TEM) [20][21][22], X-ray reflectivity (XRR) [23,24] and potentiostatic experiments (chronoamperometry) [25]. A consensus has been reached that a first-order phase transition occurs in the initial lithiation of Si, featuring the irreversible propagation of a sharp interface between the initial and lithiated amorphous phase.…”
Section: An Improved Understanding Of the Mechanisms Through Whichmentioning
confidence: 64%
See 2 more Smart Citations
“…The equilibrium crystalline phases are bypassed due to higher barriers to their nucleation compared with those of the metastable amorphous phases [16]. Similar phenomena are also observed in other alloying anodes, as well as LiMPO 4 [17,18] and Li 2 MSiO 4 [19] cathodes, for varying metals M. The mechanism of the first-cycle lithiation of Si has been intensively studied using in situ transmission electron microscopy (TEM) [20][21][22], X-ray reflectivity (XRR) [23,24] and potentiostatic experiments (chronoamperometry) [25]. A consensus has been reached that a first-order phase transition occurs in the initial lithiation of Si, featuring the irreversible propagation of a sharp interface between the initial and lithiated amorphous phase.…”
Section: An Improved Understanding Of the Mechanisms Through Whichmentioning
confidence: 64%
“…3. In a previous study of the first-cycle lithiation of Si [25], we found that the time to complete the transition strongly depended on film thickness, indicating that the irreversible phase transition initiated at the Si/electrolyte surface and propagated through the thickness of the film. In the present case, however, while the peak and total currents increase with film thickness as expected, t peak is approximately the same for all film thicknesses.…”
Section: Methodsmentioning
confidence: 81%
See 1 more Smart Citation
“…The model of Deal and Grove, which was developed to describe the growth of the oxide layer on silicon surfaces, has been well adapted to model phase transformations during electrochemical lithiation. Miao and Thompson developed a kinetic model based on the Deal–Grove model (which applies Fick's law for the case of a steady‐state flux) to elucidate the initial lithiation of amorphous silicon thin film anodes for LIBs . Another study also presented a multi‐stage model that illustrates the propagation of the Li x Si phase, the reaction rates at the interface, and the lithium diffusion behavior in crystalline silicon .…”
Section: Introductionmentioning
confidence: 99%
“…Miao and Thompson developedak inetic model based on the Deal-Grove model (which applies Fick's law for the case of as teady-state flux) to elucidate the initial lithiation of amorphous silicon thin film anodes for LIBs. [12] Another study also presented am ulti-stage model that illustrates the propagation of the Li x Si phase, the reaction rates at the interface, andt he lithium diffusion behavior in crystalline silicon. [13] For Al anodes, however,l ess information can be found regarding the kinetics of the electrochemical formation of Li-Al alloy at room temperature.…”
Section: Introductionmentioning
confidence: 99%